2014
DOI: 10.5271/sjweh.3420
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of delayed-onset post-traumatic stress disorder: a systematic review and meta-analysis of prospective studies

Abstract: This review updates earlier work by including prospective studies published within the past five years and extends earlier work by inclusion of studies with late follow-up. Addition of some recent large studies to this review brings the combined number of participants in the meta-analysis to more than five times higher than in the latest review (Smid et al, 2009).Affiliation:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
68
1
6

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(87 citation statements)
references
References 59 publications
(95 reference statements)
3
68
1
6
Order By: Relevance
“…A systematic meta-analysis of 39 prospective studies reported that 24.5% (95% confidence interval 19.5% to 30.3%) of all PTSD cases were PTSD with delayed expression. 4 Another study using data from the National Health and Resilience in Veterans Study (NHRVS) revealed that approximately 1 in 10 older United States veterans experiences a clinically significant exacerbation of PTSD symptoms in late life. A comparison of immediate and PTSD with delayed expression showed that both were similar in the number and type of symptoms reported at onset, but the delayed-onset group differed in showing a gradual accumulation of symptoms that began earlier and continued throughout their military career.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A systematic meta-analysis of 39 prospective studies reported that 24.5% (95% confidence interval 19.5% to 30.3%) of all PTSD cases were PTSD with delayed expression. 4 Another study using data from the National Health and Resilience in Veterans Study (NHRVS) revealed that approximately 1 in 10 older United States veterans experiences a clinically significant exacerbation of PTSD symptoms in late life. A comparison of immediate and PTSD with delayed expression showed that both were similar in the number and type of symptoms reported at onset, but the delayed-onset group differed in showing a gradual accumulation of symptoms that began earlier and continued throughout their military career.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Sleep disruption is considered an important feature of posttraumatic stress disorder (PTSD), 3 which is a psychiatric disorder characterized by intrusive recollections, avoidance behavior, and hyperarousal state following experience of a traumatic event. 4 A diagnosis of PTSD is made if the characteristic symptoms are present for at least 1 month after exposure to a traumatic event. Symptoms typically begin within 3 months of a traumatic exposure but it may be delayed for months or even years before the diagnostic criteria are met.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…13,14 Furthermore, posttraumatic stress disorder may have a delayed onset or increase in severity over time. 15,16 Data are available on physician visits throughout Alberta for all those (not just workers) normally resident in Fort McMurray. 17 Compared to the first week in December 2015 (before the fire), in the same week in 2016 (9 mo after the fire), physician visits for anxiety increased by 14% and for depression by 28%, whereas visits for substance use disorder decreased markedly.…”
Section: Discussionmentioning
confidence: 99%
“…Mental bozukluklarýn Tanýsal ve Sayýmsal El Kitabý 5. Baský (DSM-5)'e göre travmatik olayla ilgili istenmeyen düþüncelerin bireyin aklýna gelmesi, travmatik durumu yeniden yaþan-týlýyor gibi hissetme, olayýn hatýrlatýcýlarýndan kaçýnma ve her an kaygýlý olma hali gibi belirtilerin en az üç tanesi bireyde mevcut ise kiþi TSSB tanýsý alabilir; travmatik yaþantýnýn üzerinden en az altý ay geçtikten sonra TSSB semptomlarý görülmeye baþ-landýðý durumlarda ise kiþiye "Geç Baþlangýçlý TSSB" tanýsý konulabilmektedir (1).Utzon-Frank ve arkadaþlarý 39 prospektif çalýþmayý deðer-lendirdikleri gözden geçirme çalýþmasýnda gecikmiþ baþlangýçlý TSSB sýklýðýný %5.6, tüm TSSB'lere oranýný ise %24,5 olarak bulmuþlardýr (2). Ayrýca stresli hayat olaylarý ve TSSB'ye majör depresyon eþlik edebilir(3).…”
Section: Gýrýþunclassified